1998
DOI: 10.1007/s002990050374
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transformation of European chestnut

Abstract: Stable incorporation of the nptII gene into Castanea sativa Mill. has been achieved by Agrobacteriummediated transformation. The transformation assays were performed by infecting wounded hypocotyls with a strain of Agrobacterium tumefaciens, LBA 4404 harbouring the plasmid p35SGUSINT. Although two schemes of selection were tested, many escapes were obtained. The best strategy to avoid this problem is the introduction of higher concentrations of kanamycin in the culture medium, immediately after coculture. PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…However, it is comparable to transformation efficiencies reported for a vast majority of tree species-for example, 0.9% in apple rootstock M26 (Holefors et al 1998), 6.7% in apple rootstock M.9/29 (Zhu et al 2001), 1.5-1.8% in Castanea sativa (Seabra and Pais 1998), 7% (Confalonieri et al 2000) and 11% (Delledonne et al 2001) in Populus alba. Moore et al (1979) showed that most hairy roots emerged from the pericycle tissue of the carrot vascular cylinder.…”
Section: Discussionsupporting
confidence: 75%
“…However, it is comparable to transformation efficiencies reported for a vast majority of tree species-for example, 0.9% in apple rootstock M26 (Holefors et al 1998), 6.7% in apple rootstock M.9/29 (Zhu et al 2001), 1.5-1.8% in Castanea sativa (Seabra and Pais 1998), 7% (Confalonieri et al 2000) and 11% (Delledonne et al 2001) in Populus alba. Moore et al (1979) showed that most hairy roots emerged from the pericycle tissue of the carrot vascular cylinder.…”
Section: Discussionsupporting
confidence: 75%
“…The first report of successful Agrobacterium-mediated transformation in the Castanea genus showed transgenic shoots regenerated from European chestnut cotyledons (Seabra and Pais, 1998). This was followed by a report of the transformation of European chestnut somatic embryos that were germinated and micropropagated into whole plants (Corredoira et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…However, significant differences between 3 days and 4 days were only achieved with the strain/plasmid combination EHA105/pUbiGUSINT. A similar cocultivation period has been reported to be useful for other woody species, including apple (De Bondt et al 1994), chestnut (Seabra and Pais 1998), elm (Gartland et al 2000); 5 days of coculture was utilized in tea (Mondal et al 2001).…”
Section: Effect Of Antibioticsmentioning
confidence: 94%
“…This concentration is higher than those generally employed in other embryogenic systems of woody species such as pecan (McGranahan et al 1993) and Ginkgo biloba (DuprØ et al 2000). A similar kan level was also selected by Seabra and Pais (1998) for the transformation of chestnut hypocotyl segments. The addition of 300 mg/l carbenicillin and 200 mg/l cefotaxime, which were used to avoid the overgrowth of Agrobacterium, actually had a visible beneficial effect on the growth and multiplication of chestnut somatic embryos (data not shown).…”
Section: Effect Of Antibioticsmentioning
confidence: 98%
See 1 more Smart Citation